(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the use of new technologies and compliance with radiation safety requirements that make it possible to utilize nuclear energy as a reliable source of power. The main sources of the environmental impact of nuclear power plants are analyzed, including radioactive emissions, thermal pollution, and nuclear waste management. Particular attention is paid to modern technologies aimed at minimizing environmental risks and improving the efficiency of nuclear energy. It is noted that the sustainable development of nuclear energy is possible only with strict adherence to environmental standards and international nuclear safety regulations